The role of serotonergic mechanism in the rat prefrontal cortex for controlling the micturition reflex: An in vivo microdialysis study. Issue 8 (30th July 2015) - Chiba, Hiroki; Mitsui, Takahiko; Kitta, Takeya; Ohmura, Yu; Moriya, Kimihiko; Kanno, Yukiko; Yoshioka, Mitsuhiro; Shinohara, Nobuo
Abstract : Aims: To investigate the role of the PFC in the micturition reflex using an in vivo microdialysis study in rats. Methods: Adult female Sprague‐Dawley rats were used and microdyalysis in the PFC and cystometrography (CMG) were performed under consciousness and free movement in the present study. Experiment 1: Samples including extracellular neurotransmitters were collected by microdyalysis and analyzed by high performance liquid chromatography. At the same time, CMG were performed to measure intercontraction interval (ICI) and maximum voiding pressure (MVP).  Experiment 2: SSRI (citalopram, 1 µM) was administered into the PFC, and microdyalysis and cystometrography (CMG) were performed simultaneously. Experiment 3: Following SSRI administration, 5‐HT1A agonist (8‐OH‐DPAT, 300 µM), which has the effect of decreasing the level of serotonin (5‐HT) in the PFC, was administered into the PFC, and microdyalysis and CMG were performed simultaneously. Results: Experiment 1: Extracellular level of 5‐HT in the PFC significantly increased during micturition reflex ( P  < 0.05), whereas levels of glutamate or dopamine were not significantly changed. Experiment 2: Local administration of SSRI in the PFC increased the 5‐HT level up to approximate 600% of the basal level. It also significantly increased ICI ( P  < 0.05), whereas no significant change was found in MVP. Experiment 3: The extracellular level of 5‐HT gradually decreased after local administration of 5‐HT1A agonist, thereby ICI significantly decreased ( P  < 0.05). Conclusions: The results of the present study suggest that the PFC has a suppressive effect on neural control of the micturition reflex via serotonin. Neurourol. Urodynam. 35:902–907, 2016 . © 2015 Wiley Periodicals, Inc.